2018
DOI: 10.7575/aiac.ijels.v.6n.2p.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Memory Strategies on Iranian EFL Learner’s Vocabulary Retention in Terms of learners’ Multiple Intelligences

Abstract: This study targeted to explore the effect of memory strategy on EFL learners’ vocabulary retention with a consideration of learners’ multiple intelligence. In this study, the memory strategy consisted of three parts of grouping, acronym and images. The participants of this study were 80 male and female EFL learners of intermediate level who underwent 12 hours of instruction in a language institute. They were chosen through convenience sampling and they then were randomly divided into an experimental group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
(16 reference statements)
0
14
0
1
Order By: Relevance
“…Linguistic verbal intelligence is one of the nine multiple intelligences (MI) based on s theory of MI developed by Gardner in 1983. Intelligence mostly regarded as a one-single trait and was usually measured based on the one-dimensional concept of intelligence (IQ). Gardner's theory of MI states that this theory does not refer to just one general human intelligence (Abbassi, Hassaskhah, & Tahriri, 2018). It addresses a group of multiple intelligences, including linguistic (verballinguistic), musical, logical, visual, kinaesthetic, intrapersonal or interpersonal intelligence and naturalist and existential intelligences.…”
Section: Verbal-linguistic Intelligence (Li)mentioning
confidence: 99%
“…Linguistic verbal intelligence is one of the nine multiple intelligences (MI) based on s theory of MI developed by Gardner in 1983. Intelligence mostly regarded as a one-single trait and was usually measured based on the one-dimensional concept of intelligence (IQ). Gardner's theory of MI states that this theory does not refer to just one general human intelligence (Abbassi, Hassaskhah, & Tahriri, 2018). It addresses a group of multiple intelligences, including linguistic (verballinguistic), musical, logical, visual, kinaesthetic, intrapersonal or interpersonal intelligence and naturalist and existential intelligences.…”
Section: Verbal-linguistic Intelligence (Li)mentioning
confidence: 99%
“…111-112) stated that, "Little can be communicated without grammar, and nothing can be conveyed without vocabulary." This is further agreed by Abbassi et al, (2018) who mentioned that in our move to understand a language, a person's vocabulary is critical. Words are essential for communicating objects, acts, and opinions, according to Nation (2004).…”
Section: Introductionmentioning
confidence: 73%
“…People would definitely fail to express their intended ideas if they do not have access to language. Morra & Camba (2009) as cited by Abbassi et al (2018) stated that today, it is widely accepted that mastering a foreign language's vocabulary is one of the most important factors in both learning a native language and learning a foreign language. This is in accordance with Malaysian Education Blueprint (2013Blueprint ( -2025, in one of the eleven shifts where every child is hoped to be proficient in English as well as other languages.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of memory strategies on students' retention of words has been the topic of many previous studies (e.g., Abbasi, Hassaskhah, & Tahriri, 2018;Ghorbani & Riabi, 2011;Nemati, 2013;Sagarra & Alba, 2006). The results from these studies showed the significant impact of memory strategies on students' retention of words on the basis that these strategies succeeded in activating the human mind to conduct high level of word processing.…”
Section: Related Studiesmentioning
confidence: 97%